Penerapan model pembelajaran cooperative script untuk meningkatkan kemampuan menemukan ide pokok pada peserta didik kelas V sekolah dasar - Diana Khusnul; Rukayah Rukayah; Tri Budiharto (Universitas Sebelas Maret, 2020)
The goal of this research is to improve the ability of students in class V of Karangasem I State Elementary School Surakarta in Academic Year 2019/2020 to find the main ideas by using Cooperative Script learning model. The form of research is classroom action research. Subjects in the study found teachers and 34 students. The phase carried out in this study consisted of 2 cycles. Data collection used in this research by interviewing, gathering ability tests to find main ideas and analyzing documents. The validiity of the data used is content validity, source triangulation, and technique triangulation. The data in this study consisted of qualitative data an quantitative data. Quantitative data analysis uses comparative descriptive analysis techniques, while qualitative data uses miles and huberman analysis models. The first cycle, obtained classical completeness 52,94% and increased in the second cycle as much as 82,35%. Based on the above data it can be denied that the Cooperative Script learning model can improve the ability of students to find the main ideas in grade V students of Karangasem I Elementary School Surakarta in the academic year 2019/2020.